A cold atom apparatus for the microscopy of thin membranes - GADGE, AMRUTA (2018)
Ultracold atomic gases can be utilised as extremely sensitive probes of their surrounding environment. In particular, samples of ultracold atoms confined using chip-based microtraps are an ideal tool for mapping electric and magnetic field landscapes. Over the course of this thesis, a new experiment capable of performing surface microscopy using magnetically trapped clouds of cold rubidium-87 atoms has been built. The focus of the work is on the design and construction of the experimental system, which must incorporate many different aspects for manipulating thermal atomic gases, with a view to positioning them at sub-micron distances from special surfaces. This reduced atom-surface separation is necessary for implementing a high resolution, high sensitivity magnetic field sensor with cold atoms.